The Effect of Product Quality and Service Quality on Consumer Satisfaction Mediated by Mixue Product Purchase Decisions - Anggela, Nova; Helmi, Sulaiman; Heriyanto; Septayuda, Irwan (Yayasan Sinergi Kawula Muda, 2024)
With the large spread of Mixue outlets in Palembang, several problems have arisen, such as product quality and service quality that are felt different and not good. This study aims to analyze the influence of product quality and service quality on consumer satisfaction mediated by the decision to purchase Mixue products. This study uses a quantitative method by distributing questionnaires to 100 respondents who bought Mixue in Palembang. The sample used was an ingenious sampling technique (unintentional/accidental sampling). Data analysis uses the help of SmartPLS 4 by evaluating the measurement model (another model), structural model (inner model), and hypothesis testing. The results of the study show that product quality has a significant influence on the purchase decision of Mixue products, product quality has a significant effect on Mixue consumer satisfaction, service quality has a significant influence on the purchase decision of Mixue products, service quality has a negative and insignificant effect on consumer satisfaction. Purchase decisions have a significant effect on consumer satisfaction with Mixue products.